Mixed Metal Oxide Mesoporous Nanoparticles For Environmental Remediation - Davis, Nithya; P, Usha Rajalakshmi; T, Sakthivel (Kongunadu Research Journal, 2019)
Mesoporous mixed metal oxides (SnO2(x) -TiO2 (1-x) , x= 0.75,0.50 and 0.25) were synthesized by evaporation induced self assembly using cationic surfactant, Cetyl Trimethyl Ammonium Bromide (CTAB) as the structure directing agent. The small angle X-ray diffraction pattern of mesoporous SnO2 and SnO2-TiO2 mixed metal oxides revealed the presence of well defined mesostructure in the metal oxides. The mixed metal oxide system has crystallized in orthorhombic structure, resembling the host lattice. Mesopore channels were collapsed upon calcinations at 550°C. The optical absorption of the SnO2 has been extended into the visible region upon incorporation of “Ti”. A remarkable enhancement of the photocatalytic degradation efficiency (60% ) of (SnO2(0.5) -TiO2 (0.5) was observed against aqueous solution of methylene blue dye.